Analysis of Pre-and Post-operative Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio in Acute Kidney Injury After Coronary Artery Bypass Grafting Surgery - Lonasis Cabuslay; Lopa AT; Wibawa SY; Rauf DE (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Acute Kidney Injury (AKI) remains a common complication of post-operative Coronary Artery Bypass Grafting (CABG) related to high morbidity and mortality. Systemic inflammation has been known as a part of the pathogenesis of acute kidney injury. This study aimed to analyze the Neutrophil Lymphocyte (N/L) ratio and Platelet Lymphocyte (P/L) ratio in post-operative AKI. This research was a retrospective study involving 76 patients who underwent CABG surgery in Dr. Wahidin Sudirohusodo Central Hospital, Makassar, between January 2015 and May 2019. The diagnosis of AKI was based on Kidney Disease Improving Global Outcomes (KDIGO) 2012 criteria. The N/L ratio and P/L ratio were calculated respectively as a neutrophil count ratio to lymphocyte count and platelet count to lymphocyte count. Twenty-five (32.9%) patients developed AKI in the first 48 hours of the post-operative period. There was no difference in pre-operative N/L ratio and the P/L ratio between AKI and non-AKI groups (p > 0.05). Both ratios increased after surgery and were significantly different between the two groups with higher mean ratio in non-AKI (16.93±9.16 vs. 21.86±11.13, p=0.040 and 239,24±184,36 vs. 314,49±143,73, p=0.011). Both pre-operative and post-operative N/L ratio and P/L ratio could not distinguish AKI after CABG.